SYSTEMATIC REVIEW AND META-ANALYSIS: PITFALLS OF METHODS - Yu. V. Lukina; S. Yu. Martsevich; N. P. Kutishenko (Рациональная фармакотерапия в кардиологии)
Methods that allow to systematize the accumulated information on specifically formulated questions, analyze it and make reliable findings are of great interest and popularity with the emergence of a huge number of studies and publications in various fields of medicine, a significant increase in information, failure to identify weak effects in the individual studies. The use of systematic reviews and high-quality meta-analysis is an analytical basis of evidence-based medicine, it is a very valuable tool for decision-making at the level of practitioner, health care leaders and experts in the preparation of guidelines and legislation concerning the use of the most effective and safe treatments, when planning future research, in the development of rational health policy. Features of methods of systematic review and meta-analysis and their strengths and weaknesses are discussed in the article. The authors present the historical facts of occurrence of the Cochrane Collaboration, whose main task is to systematize and analyze accumulated information from a variety of medical research. The contribution of Russian researchers into this field of medical science is also assessed.